Time-variant attribute-based multitype encryption algorithm for improved cloud data security using user profile - Kumaresan, S.; Shanmugam, Vijayaragavan (The Journal of supercomputing, 2020)
Cloud computing becomes more sophisticated to provide different services at different levels of user access. Even though various services are accessed at a different level, the security of data being accessed is a highly challenging one. However, there is a number of encryption approaches discussed toward the problem of cloud security; they suffer to achieve higher security as required. The previous ABFD (attribute-based flexible delegation) algorithm uses a set of policies in encrypting the data with specific keys mentioned in the policy. However, the leakage of encryption policy would introduce poor security which can be overcome by adopting multitype encryption standards in different time windows. According to this, an efficient time-variant attribute-based multitype encryption algorithm (TAM) is presented in this paper. The TAM algorithm maintains a taxonomy of attributes and related keys to be used for encryption and decryption. The corresponding keys have been used to generate the ciphertext. The content of taxonomy has been dynamically changing in each time window which makes the difference in integrity management and security performance than previous algorithms. The TAM approach introduces a higher security performance up to 89.6%. The method also reduces the time complexity up to 21 s and increases the throughput performance up to 96%.